2010
DOI: 10.1007/s00464-010-1311-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex is not everything: the role of gender in early performance of a fundamental laparoscopic skill

Abstract: Gender did not affect the learning curve for a fundamental laparoscopic task, while interest in surgery and perceptual abilities did influence early performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 31 publications
6
54
3
Order By: Relevance
“…Applying a nonlinear regression curve-fitting technique to analyze the learning curve for early performance yields an estimation of the performance plateau and the rate of improvement [11]. Using this technique, we found that the PT learning plateau was lower [11] and the rate of improvement slower [12] for medical students with low selfreported interest in a surgical career. This suggests that learning plateau and rate may be useful outcomes for educational interventions designed to have an impact on the learning curve.…”
Section: Resultsmentioning
confidence: 96%
“…Applying a nonlinear regression curve-fitting technique to analyze the learning curve for early performance yields an estimation of the performance plateau and the rate of improvement [11]. Using this technique, we found that the PT learning plateau was lower [11] and the rate of improvement slower [12] for medical students with low selfreported interest in a surgical career. This suggests that learning plateau and rate may be useful outcomes for educational interventions designed to have an impact on the learning curve.…”
Section: Resultsmentioning
confidence: 96%
“…Despite an advantage of females regarding palpatory diagnostic competencies in our study, students of both genders achieved comparable results during practical manipulative assessment. Recently, Kolozsvari et al [27] stated that gender does not affect the learning curve for a bimanual demanding motor skill (laparascopic task), while surgical interest and perceptual abilities influence the early outcome. All students were less satisfied with the teaching of the student-teachers compared to professionals, but female students consistently rated the knowledge transfer by student-teachers better than male students.…”
Section: Discussionmentioning
confidence: 99%
“…Applying a nonlinear regression curvefitting technique to analyze the learning curve for early performance yields an estimation of the performance plateau and rate of improvement [63]. Using this technique, we found that the peg transfer learning plateau was lower [63] and the rate of improvement was slower [64] in medical students with low selfreported interest in a surgical career, suggesting that learning plateau and rate may be useful outcomes for educational interventions designed to impact the learning curve.…”
Section: Manuscript: Mastery Versus Standard Proficiencymentioning
confidence: 98%